Traditional Thai Music Competition: The Culture of Pipat Competition - Veera Phansue (IJCAS (International Journal of Creative and Arts Studies), 2014)
The title of this research is “The Culture of Pipat Competition” has three purposes as follows: 1) To study the knowledge of Pipat competition; 2) To study the process of Pipat competition; 3) To study the process of judging and deciding a Pipat competition. This research used the qualitative method and presented the research by using descriptive analysis. The results found that; 1) The knowledge of Pipat competition. The competition is to bring ensembles to perform their skills and abilities. Mostly, in a Pipat ensembles the knowledge and skills displayed are governed by a definite set of form and rules during the competition. Only the Pipat Mon that there is no any form or rule in the competition. The ensembles that want to join the competition have to prepare very well in term of musicians and place for rehearsal before the event. Moreover, the conductor of ensemble has to be highly skilled and experienced in coming up with a new technique for playing in order to take an advantage over the rivals. And the conductor should know the strength and weakness of the rivals too. 2) The Study of the process of Pipat competition. The competition has a certain set of forms and rules. The detail of forms and rules will be set by each competitor agreement and it is very easy for practice. It is different from the competition that there is no form or rule so, this kind of competition, the musicians should have a lot of knowledge and in an easy and a relax ways without strict rule, form or time in the competition many kinds of songs will be played. Therefore the conductor must plan everything for the competition. There are 2 types of competition; 1) different song, each ensembles will take turn to play a song and begin with the basic melody until the highly complicated notes and those songs must be in the same style. 2) same song, each ensemble plays same song simultaneously during the whole competition. This kind of competition is very serious and if any of the ensemble cannot play or keep pace with the melody it means they lose the competition. 3) Study of the process of deciding and judging a Pipat competition. There are 3 types of judging in the Pipat competition. 1. The musician and the singer know the result by themselves. 2. The audience decides who wins the competition. 3. The judge decides who wins the competition. The advantage of decision is choosing the best ensemble with developed technique and playing method while the disadvantage is when the musicians do not accept the decision often leading to quarrel and disharmony.